(untitled) (Modern Problems of Metallurgy, 2022)
Today, there are technologies for recycling lithium power sources, but they are not yet satisfactory and cost-effective. The purpose of the study - based on the analysis of scientific and technical publications to formulate a general description of modern technologies for recycling lithium power sources. The second purpose is to present the results of the authors’ research on the improvement of lithium battery recycling technologies. Based on the analysis of scientific and technical publications, a general description of modern technologies for processing lithium power sources is given. Processing is carried out according to the following scheme. First, they organize the discharge of power sources and their pre-treatment to separate the active substances. Pre-treatment is carried out by mechanical grinding, or ultrasound, or calcination or solvents. Mechanical crushing is performed in blade crushers. Machining is the most common method of separating lithium batteries. However, it has disadvantages: loud noise, emissions of dust and harmful gases. Calcination takes place at temperatures up to 500 ° C to remove carbon and organic material. Disadvantages of the method: calcination requires expensive equipment, is energy-intensive and can emit toxic gases. Solvent pre-treatment uses solutions and solvents to separate the active materials from Al, Cu foil in the battery. This method removes the addition of binder material, which increased the contact of the foil with the active materials. Disadvantages: this method requires the use of hot organic solvents of about 100˚C, which increases the cost and creates hazardous waste into the environment. More promising is the method of processing batteries in ultrasonic cavitation. The pre-treated material is subjected to magnetic or gravitational separation, removing substances containing metals. Then Li, Co, Ni, Mn are removed by pyrometallurgy, or hydrometallurgy, or electrochemical extraction. The obtained metals are suitable for secondary use in lithium power sources. The analysis of the considered technologies of processing of lithium power sources indicates that an important way to increase the efficiency of recycling is to improve the quality of pre-treatment of products that have exhausted the resource, which allows to effectively remove active materials with the lowest energy costs and environmental risks. The authors have developed a schematic diagram of the technology of pre-treatment of lithium batteries based on acoustic or hydrodynamic cavitation, as well as improved the method of magnetic separation of metals.